The potentially beneficial central nervous system activity profile of ivacaftor and its metabolites. Issue 1 (13th March 2018) - Schneider, Elena K.; McQuade, Rachel M.; Carbone, Vincenzo C.; Reyes-Ortega, Felisa; Wilson, John W.; Button, Brenda; Saito, Ayame; Poole, Daniel P.; Hoyer, Daniel; Li, Jian; Velkov, Tony
Ivacaftor–lumacaftor and ivacaftor are two new breakthrough cystic fibrosis transmembrane conductance modulators. The interactions of ivacaftor and its two metabolites hydroxymethylivacaftor (iva-M1) and ivacaftorcarboxylate (iva-M6) with neurotransmitter receptors were investigated in radioligand binding assays. Ivacaftor displayed significant affinity to the 5-hydroxytryptamine (5-HT; serotonin) 5-HT2C receptor (p K i =6.06±0.03), β3 -adrenergic receptor (p K i =5.71±0.07), δ-opioid receptor (p K i =5.59±0.06) and the dopamine transporter (p K i =5.50±0.20); iva-M1 displayed significant affinity to the 5-HT2C receptor (p K i =5.81±0.04) and the muscarinic M3 receptor (p K i =5.70±0.10); iva-M6 displayed significant affinity to the 5-HT2A receptor (p K i =7.33±0.05). The in vivo central nervous system activity of ivacaftor (40 mg·kg −1 intraperitoneally for 21 days) was assessed in a chronic mouse model of depression. In the forced swim test, the ivacaftor-treated group displayed decreased immobility (52.8±7.6 s), similarly to fluoxetine (33.8±11.0 s), and increased climbing/swimming activity (181.5±9.2 s). In the open field test, ivacaftor produced higher locomotor activity than the fluoxetine group, measured both as mean number of paw touches (ivacaftor 81.1±9.6 versus fluoxetine 57.9±9.5) and total distance travelled (ivacaftor 120.6±16.8 cm versus fluoxetine 84.5±16.0 cm) in 600 s. Treatment of 23 cystic fibrosis patients with ivacaftor–lumacaftor resulted in significant improvements in quality of life (including anxiety) in all five domains of the AweScoreCF questionnaire (p=0.092–0.096). Our findings suggest ivacaftor displays potential clinical anxiolytic and stimulating properties, and may have beneficial effects on mood. The novel CFTR potentiator ivacaftor displays potential pre-clinical and clinical anxiolytic and antidepressant properties, which may have beneficial effects on mood and well-being in CF patients receiving ivacaftor or ivacaftor–lumacaftor therapy http://ow.ly/thK430iaigr